Modifiable factors associated with neuropsychiatric symptoms in nursing homes: The impact of unmet needs and psychotropic drugs. (January 2020) - Ferreira, Ana Rita; Simões, Mário R.; Moreira, Emília; Guedes, Joana; Fernandes, Lia
Highlights: In nursing homes, neuropsychiatric symptoms (NPS) are particularly frequent. Cognition, functional status, needs and psychotropic drugs all correlate with NPS. Unmet needs and hypnotic/sedatives shown to increase the risk of presenting NPS. Identifying and modifying these factors would benefit residents' symptomatology. Findings conform with the unmet needs model, placing emphasis on needs assessment. Abstract: Objective: This study aimed to explore neuropsychiatric symptoms' (NPS) risk factors in a sample of nursing home residents. Methods: A cross-sectional study was conducted. Residents over 65 years were included, unless they had a known major psychiatric diagnosis. The Neuropsychiatric Inventory (NPI) was completed, and other measures included residents' sociodemographic characteristics, cognition, functional impairment, regular drugs and number of needs. To explore potential risk factors, a logistic regression was conducted with the presence of NPS (NPI-10 ≥ 1) as dependent variable. Additional exploratory analyses were conducted based on a sub-syndrome approach, and three multivariate models were repeated considering the psychotic, affective and behaviour syndromes as dependent variables. Results: A total of 140 residents were included (age: 83.71 ± 7.29 years). More than half (50.4%) presented at least one NPS. NPI-10 showed significant correlations with cognition (rs =-0.177, p  = 0.042), functional impairment (rs  = 0.174, p  = 0.043), unmet needs (rs  = 0.245, p  = 0.004) and nervous system-acting drugs (rs  = 0.271, p  = 0.002), particularly anxiolytics (rs  = 0.175, p  = 0.047), antidepressants (rs  = 0.204, p  = 0.019) and hypnotics/sedatives (U = 2434.5, p  = 0.028). However, in the multivariate analysis only unmet needs (OR = 1.30; 95% CI: 1.008–1.670) and hypnotic/sedatives (OR = 4.66; 95% CI: 1.132–19.144) showed an independent association with the presence of NPS. Regarding the additional models, unmet needs and literacy, antidepressants and hypnotic/sedatives, and cognitive status, showed to contribute to explain the variability of psychotic, affective and behaviour syndromes, respectively. Conclusions: Identifiable and modifiable factors, including unmet needs and prescribed psychotropic drugs, could have contributed to NPS in this sample, suggesting a role for targeted non-pharmacological and person-centred approaches directed to residents' unmet needs.